Treatment of neuro-invasive listeriosis: an overview - Gudeikaitė , P.; Valaikienė , J.; Mameniškienė , R. (Neurologijos seminarai, 2018)
Increasing mortality and morbidity rates of neurolisteriosis in Lithuania and Europe require methodological standardized treatment and a rapid response to the patient’s serious condition. Listeria monocytogenes is an aerobic gram-positive bacillus that can cause invasive listeriosis in humans, which most commonly affects the central nervous system. Clinically, neurolisteriosis occurs as meningoencephalitis, which is associated with the highest mortality rate in patients with severe conditions. The most at-risk populations are pregnant women, neonates, people over 65 years of age, and patients with chronic diseases or using immunosuppressive drugs. In case of suspected acute meningitis, encephalitis or meningoencephalitis in these individuals, it must be considered that the pathogen can be Listeria monocytogenes, which is resistant to the therapy of cephalosporins. First-line recommended therapy is a combination of amoxicillin and gentamicin intravenously. If the patient is allergic to beta-lactams, therapy of co-trimoxazole is recommended. The administration of dexamethasone against neurolisteriosis increases mortality rate. The article reviews the clinical manifestation and diagnostic criteria of neuroinvasive listeriosis and provides treatment recommendations.